Evaluation of the Health Information System in Teladan Public Health Center in 2020 Using the Health Metrics Network Instrument Approach - Anggun Hasanah; Delia Nurrahmah Rangkuti; Gisa Zel Dita Pinem; Fauziah Nasution (Pena Cendekia Insani, 2021)
The Health Information System is an integrated system that systematicallymanages public data and information (Government, community and private) atall levels of government to support health development in a health facility.This description can be known by conducting a Health Information System(HIS) evaluation activity. This study aims to determine the description of thehealth information system at the Teladan Health Center in Medan City. Theresearch was conducted at the Medan City Teladan Public Health Center,North Sumatra, in June 2019. The subject in this study was the Head of theAdministrative Subdivision of the Teladan Public Health Center, which wastaken based on purposive sampling. The data were gathered through directinterviews and observations. We are using the triangulation method todetermine the data's validity. With a percentage of 73%, health informationsystem resources are classified as